Where and how - new insight for brown algal forest restoration in the Adriatic - Orlando-Bonaca, Martina; Savonitto, Gilda; Asnaghi, Valentina; Trkov, Domen; Pitacco, Valentina; Šiško, Milijan; Makovec, Tihomir; Slavinec, Petra; Lokovšek, Ana; Ciriaco, Saul; Chiantore, Mariachiara; Kaleb, Sara; et al. (Frontiers in Marine Science, 2022)
Several anthropogenic factors are responsible for the decline of Cystoseira sensu lato (hereafter Cystoseira) forests along Mediterranean coasts. Some Cystoseira species are already regionally extinct, and their decline has been widely recorded. Sustainable and efficient techniques for the restoration of Cystoseira are needed. In this context, the objectives of this study were i) to analyse the reproductive traits of three populations of Gongolaria barbata from three nearby donor sites in the northern Adriatic Sea, assessing the differences in their reproductive potential and reproductive success; and ii) to evaluate the outplanting success in terms of the effectiveness of G. barbata restoration, in relation to the different donor and receiving sites (Miramare MPA and in front of the Marine Biology Station Piran - MBSP) and implemented methods (ex situ and hybrid method combining a mesocosm cultivation and a suspended culture in the field). After 2 weeks of cultivation in mesocosms, half of the tiles with germlings were transported to the receiving sites and placed on suspended lantern nets (hybrid method), which were later (after 3 months) transferred to the seabed on concrete plates with protective cages. The remaining tiles were placed on the seabed on concrete plates with protective cages after a 4-week culture (ex situ method). At both sites, lantern nets and plates were randomly placed at 3 m depth. Thallus length was measured monthly in each treatment. Seedlings in suspended culture showed lower performance at the Miramare MPA, most likely due to the unfavourable environmental conditions. The satisfactory results obtained at MBSP demonstrate the efficiency of the hybrid method and confirm its potential to reduce the cost and time required for cultivation. Since unpredictable climatic events pose the greatest threat to restoration performance, these challenges must be considered when establishing new restoration practices. Moreover, herbivore regulation is extremely urgent and should be planned and implemented on a larger regional scale.